MEMBRAN POLYETHERSULFONE DAN REGENERATED CELLULOSE UNTUK ULTRAFILTRASI - Trismilah, Trismilah; Lutfi, Achmadin (Jurnal Sains dan Teknologi Indonesia, 2009)
Purification of xilanase result of fermentation from Bacillus stearothermophilus DSM 22 using membrane polyethersulfone and regenerated cellulose, each measuring 30 kD. Variations in pH 4.94, 5.80, 6.60, 7.40, 8.20. Analysis of enzyme activity, protein content and enzyme specific activity carried out on permeate and retentate. This study aimed to learn the best pH condition and the appropriate type of membrane process in the purification method xilanase with ultrafiltrasi. Research of resultsindicate that pH is very influential in the process ultrafiltration xilanase, each membrane has a different characteristic. Purification xilanase best use of ultrafiltration membrane polyethersulfone achieved in the pH 4.94 with a specific activity 13,888 U / mg in the permeate. Purification xilanase best ultrafiltration use of regenerated cellulose membrane at pH 8.20 achieved with specific activity 12397 U / mg in the retentate.